Global hotspots and trends in research on preschool children’s motor development from 2012 to 2022: a bibliometric analysis - Wang, Jun-Wei; Qu, Sha; Zhu, Zhi-Cheng; Zhao, Xing; Song, Wen-Jing; Li, Xue; Chen, Wan-Di; Luo, Dong-Mei (Frontiers in Public Health, 2023)
Background Motor development plays an important role in human development throughout the lifespans, from conception to death, and has received increasing scholarly attention in recent years. However, valuable comprehensive reviews and literature analysis on this topic are still lacking. Here, this bibliometric study aimed to identify global motor development research hotspots and trends on preschool children’s motor development from 2012 to 2022. Methods CiteSpace 6.1.R4 was used to visualize and analyze general bibliometric characteristics, research hotspots, and trends through a review of 2,583 articles on the motor development of preschool children, which were published from 2012 to 2022 and included in the Web of Science Core Collection. Results Research on motor development in preschool children has been carried out into a phase of rapid development. The top five frequently occurring keywords were physical activity (n = 489), performance (n = 319), intervention (n = 222), health (n = 196), and executive function (n = 165); The top five keywords in terms of centrality are academic achievement (0.22), low birth weight (0.16), association (0.14), brain (0.13), and cerebral palsy (0.13). Thirteen keyword clusters were produced from the log-likelihood ratio (Q = 0.74, S = 0.88), and five research topics has been received focused attention in recent years. The keywords with the strongest citation bursts in the last 5 years are developing country (S = 5.92), school-aged children (S = 5.86), middle-income country (S = 3.46), efficacy (S = 5.41), readiness (S = 3.21), motor proficiency (S = 3.6), and screen time (S = 3.3), indicating newly emerging research trends. Conclusion The results indicated that interventions involving fundamental movement skills, cognitive function, 24-h movement behaviors, neurodevelopmental disorders, and health-related fitness were hot topics in the field of motor development over the last decade. Emerging research trends generally center on school readiness, socioeconomic status, motor proficiency, and screen time.